2019
DOI: 10.1123/jpah.2017-0437
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Cognitive Control Performance During Seated Rest and Self-Paced Cycling on a Desk Bike in Preadolescent Children

Abstract: Background: Although active workstations, such as desk bikes, have proven to be beneficial for health, there is limited information regarding their effects on children’s acute cognitive performance during self-paced exercise. Methods: This study used a within-subjects, fully counterbalanced design with a sample of 38 preadolescent children (mean age = 12.50 y, SD = 0.62; 43% male), who performed cognitive tests while being seated or while cycling for 45 minutes with a 7-day interval. Effects of using a desk bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
2
0
3
Order By: Relevance
“…Most research in the acute exercise literature has found positive effects on cognitive control processes after at least 20 min of moderate exercise (e.g., Hillman et al, 2003) in adults. To our knowledge, very few studies have investigated the effectiveness of a seated concurrent light intensity physical activity for preadolescents or adolescents diagnosed with ADHD (Sarver et al, 2015;Ruiter et al, 2019). Therefore, in the present study, the effects of structured motor activity on a desk bike on phonological WM performance in adolescents diagnosed with ADHD were examined.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most research in the acute exercise literature has found positive effects on cognitive control processes after at least 20 min of moderate exercise (e.g., Hillman et al, 2003) in adults. To our knowledge, very few studies have investigated the effectiveness of a seated concurrent light intensity physical activity for preadolescents or adolescents diagnosed with ADHD (Sarver et al, 2015;Ruiter et al, 2019). Therefore, in the present study, the effects of structured motor activity on a desk bike on phonological WM performance in adolescents diagnosed with ADHD were examined.…”
Section: Introductionmentioning
confidence: 98%
“…As a response to these negative developments, organizations have begun to promote physical activity in the classroom (National Association for Sport and Physical Education et al, 2008). In addition, there has been a gradual increase in studies investigating the impact of active teaching lessons or active workstations on health and cognition (see also Kibbe et al, 2011;Donnelly et al, 2016; for a review see Mavilidi et al, 2018;Ruiter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…El profesor en general, y el profesor de Educación Física en particular, son ejemplo y modelo del adolescente, si estos propician un ambiente escolar activo y transmiten la ilusión por el deporte lo más probable es que este hábito permanezca en el alumnado a lo largo del tiempo (Cothran et al, 2010;Mavilidi et al, 2019). En este estudio se seleccionaron los dispositivos bike desks porque el pedaleo es una actividad saludable (Oja et al, 2011), donde ni las diferencias de género ni de competencia motriz condicionan su práctica, ni hay desmotivación por no lograr los objetivos (Ruiter et al, 2019). Finalmente, con este programa se abordó el reto de Salud, Cambio Demográfico y Bienestar, uno de los ocho retos incluidos en el Plan Estatal de Investigación Científica y Técnica y de Innovación (Gobierno de España, 2017) y se buscó contribuir para alcanzar el ODS número 3 que buscar garantizar una vida sana y promover el bienestar para todos en todas las edades (United Nations, 2015).…”
Section: Justificación De La Investigaciónunclassified
“…Así, la intervención PEDAL de lecciones activas con bike desks intentó alcanzar dicho reto influyendo positivamente en la actividad física general de los estudiantes y reduciendo su sedentarismo en la escuela, todo ello sin que se viese comprometido su rendimiento académico. Por tanto, como ya afirmaron Ruiter et al (2019), se podría considerar, una vez analizados los resultados, que las bike desks son una buena estrategia para implementar en las escuelas. El siguiente paso sería comprobar si es una estrategia que educa a largo plazo para que los niños y adolescentes sean agentes activos de su salud (Llargués et al, 2017) o una medida con resultados puntuales.…”
Section: Viabilidad: Beneficiosunclassified
See 1 more Smart Citation